Identifikasi Tumbuh Kembang Anak Usia 0-1 Tahun - Aryuni Hidiyatati; Heny Laylatul Qodriyah Sittati; Isnaini Azis Yuliastuti (Universitas Muhammadiyah Klaten, 2025)
Monitoring the growth and development of children aged 0-1 years is very important for monitoring their health and development. Here are some important points. First, Growth and Development Monitoring, where parents and caregivers need to monitor the growth and development of children regularly to detect potential health or developmental problems. Second, Growth and Development Indicators. Some indicators that need to be monitored include weight, height, head circumference, motor skills, and cognitive abilities. Third, Signs of Issues: If a child does not reach certain developmental milestones, such as being unable to lift their head or respond to sounds, further evaluation is necessary. Fourth, the Role of Parents: Parents play a crucial role in monitoring their child's growth and development and intervening early if needed. By detecting issues early, we can help children reach their full potential and prevent future health or developmental problems. The urgency of early identification of infant development in the first year of life is increasingly important, given that this period is also vulnerable to the effects of family stress, domestic violence, poverty, and unresponsive caregiving. Warm and consistent interaction between infants and their primary caregivers is the foundation for healthy brain development. When these risk factors are not identified early on, infants are at risk of developmental disorders that can have long-term impacts on academic achievement, mental health, and quality of life in adulthood. Therefore, systematic efforts are needed to identify children's growth and development from an early age to ensure timely, appropriate, and targeted interventions